Impact of COVID-19 pandemic on food supply chain: An overview. Issue 1 (October 2021) - Baltic, T; Rajic, S; Ciric, J; Brankovic Lazic, I; Djordjevic, V; Velebit, B; Geric, T
Abstract: Since 2020, the rapid spread of the SARS-CoV-2 virus has caused the global pandemic COVID-19, generating health, economic and social impacts. The rapid spread of the infection in the human population required an accelerated adaptation to the new circumstances to protect human health and mitigate financial losses. As the ongoing pandemic has caused reported cases in the multi-millions, all stakeholders need to prevent further outbreaks and mitigate associated risks. Hence, besides government, health care systems, business stakeholders, public authorities, non-governmental organizations, and other socially responsible associations, the food sector has a crucial role in combating COVID-19. The food sector in this context is referred to as every actor in the food supply chain. This paper explores the difficulties in the entire food supply chain's reactions to the pandemic crisis and underlines the meat sector's response.